Prevalence of Mycoplasma Gallisepticum in Domestic Chickens and Free Flying Birds and Molecular Characterisation of the Isolates - Jaganathan, Mahadevan (2006)
Chronic respiratory disease (CRD) and complicated chronic respiratory disease (CCRD) are caused by Mycoplasma gallisepticum (MG). Infected birds show respiratory and reproductive problems which lead to severe production losses in poultry industry. Mycoplasma gallisepticum has been isolated in chickens and free flying birds (FFB) in several parts of the world. Therefore the current study was carried out to determine the prevalence of MG infection, also to molecularly characterize MG isolated from commercial chickens (broilers and layers), multiflock birds (indigenous chickens, ducks, turkeys and guinea fowls) and FFB in Selangor. This study showed that using fresh yeast extract in preparation of mycoplasma agar and taking samples from choanal site of birds have made isolation of MG possible especially in layer chickens and indigenous chickens. Twenty-seven (27) MG isolates were isolated from layer birds and indigenous chickens. The recovery rate by culture method was lower compared to the detection rate by DNA profiling using Polymerase chain reaction (PCR). Excessive usage of antibiotics in broiler farms may have contributed to the failure to isolate MG from broiler chickens by culturing method. The attempt to isolate MG from FFB was unsuccessful due to the small anatomical structure of choanal cleft and high contamination of oral cavity of FFB. The latter may have hindered the growth of MG artificially. Therefore, this study also proved that PCR is a better tool for epidemiological study compared to culturing method. Broiler chickens and FFB at farms showed a high prevalence of MG infection based on serology and DNA detection but isolation could not be isolated. Crows from non-farm area or were not in close contact with infected birds or farms, did not show evidence of MG infection. This study also shows that only clinically ill infected birds, excreted and spread the organism to other flocks or species, as observed in the crows from the infected farm. However, sub-clinically infected birds as in indigenous chickens did not transmit the organism to other chickens or birds. Characterisations of the MG isolates were conducted to investigate the presence of one or more types of MG strain in this study. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and restriction endonuclease analysis (REA) were used as characterisation tools. All MG isolates from commercial chickens showed a unique band at 75 kilo-Dalton in SDS-PAGE, which was an important characteristic of MG F strain, which suggested that the isolates from layer farms could have derived from MG F strain, whereas the isolates from indigenous chickens were not similar to MG F strain. Different environmental exposures by MG strain may have caused alternation in genotype and/or phenotype, which might vary from one farm to another farm. Thus, these MG strains might reveal different patterns in REA and SDS-PAGE. It is possible that the genotypic and phenotypic heterogeneity of MG demonstrated in the present study may have adversely influenced the outcome of the serum agglutination serology and may be important to consider optimizing antibody and organism detection systems. However, the unique characteristic of MG strain was reported to be stable when tested by SDS-PAGE. Whereas, based on REA, only one strain of MG will circulate among the flock of a farm. This study therefore shows a high evidence of MG infection in commercial birds and FFB in farm. All MG isolates recovered from layer chickens were identical and possess a unique 75 kilo-Dalton protein band which was specific for MG F. However, the MG isolates obtained from the indigenous chickens were different from MG F strain .Their origin could not be determined from this study.